2012
DOI: 10.1111/j.1542-4758.2012.00757.x
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxemia after high cutoff hemodialysis for treatment of patient with multiple myeloma can be prevented by using ultrapure dialysate: A case report

Abstract: To report endotoxemia presented in a case with multiple myeloma (MM) treated by high cutoff hemodialysis (HCO-HD) being prevented by using ultrapure dialysate. A female inpatient with MM received six times HCO-HD (HCO 2100 dialyzer) within 3 weeks after initiation of a chemotherapy based on vincristine+epirubicin+dexamethasone protocol. Conventional dialysate was used in the first three times and then changed to ultrapure dialysate due to elevation of body temperature after HCO-HD. Free light chains (FLC) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…If the use of larger pore membranes would result in a substantial transmembrane transport of bacterial degradation products in settings with poor water quality, the positive effects of this type of membranes on inflammation could potentially be completely annihilated by the added inflammatory burden induced by these translocated contaminants. A case-study by Gong et al reported a risk for endotoxemia when using an HCO membrane in combination with conventional dialysis fluid (0.112–0.141 EU/ml) [ 43 ]. However these results rely on a single measurement and as reviewed by Wong et al caution should be taken when measuring endotoxin levels in blood using the LAL assay as its sensitivity and specificity for biological samples is poor [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…If the use of larger pore membranes would result in a substantial transmembrane transport of bacterial degradation products in settings with poor water quality, the positive effects of this type of membranes on inflammation could potentially be completely annihilated by the added inflammatory burden induced by these translocated contaminants. A case-study by Gong et al reported a risk for endotoxemia when using an HCO membrane in combination with conventional dialysis fluid (0.112–0.141 EU/ml) [ 43 ]. However these results rely on a single measurement and as reviewed by Wong et al caution should be taken when measuring endotoxin levels in blood using the LAL assay as its sensitivity and specificity for biological samples is poor [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increase in the pore sizes of HCO membranes translates into an increase in both the convective and diffusive permeability, thus allowing for the removal of molecules, such as mediators of sepsis/inflammation ( 18 ), or the removal of nephro-toxic light chains of immunoglobulins ( 19 ). However, the albumin loss with this membrane is substantial, from approximately 9 to 23 g/treatment ( 20 , 21 ), and it is not indicated for use in chronic dialysis but instead is recommended mainly for acute applications ( 22 ).…”
Section: Development Of Dialysis Membranes With Different Permeabilitmentioning
confidence: 99%
“…At the end, 3 case reports [15,16,17], 3 studies on animals [18,19,20], 11 in-vitro/ex-vivo studies [13,21,22,23,24,25,26,27,28,29,30,] and 6 randomized clinical trials/observational studies [14,31,32,33,34,35] fulfilled optimum criteria. The main results deriving from this pool constitute this review.…”
Section: Introductionmentioning
confidence: 99%